Assessment of mental health and psychosocial support needs and resources among earthquake-affected communities in Nepal (TPO Nepal Peae of Mind, 2016)
Executive Summary: This report details the results of a mental health and psychosocial support resource and needs assessment in Kathmandu, Gorkha, and Sindhupalchowk districts, three of the most affected areas in Nepal following the earthquakes of April 25 and May 12, 2015. The assessment was conducted in August-September 2015 by the Transcultural Psychosocial Organization Nepal (TPO Nepal) and supported by International Medical Corps (IMC) whose emergency response operations started directly after the earthquakes.